Genetic variation for biochemical traits in aroeira seeds derived in anthropized population - Pupin, Silvelise [UNESP]; Ribeiro Junior, Walter Aparecido [UNESP]; Alzate-Marin, Ana Lilia; Moraes, Marcela Aparecida de [UNESP]; Silva, Janaina Rodrigues da [UNESP]; Teixeira de Moraes, Mario Luiz [UNESP] (Univ Federal Mato Grosso, 2017)
Genetic quality of forest seeds are essential for populations foundation, as well as, the chemical composition is essential to maintain the vigor and support the establishment of the seedlings in the plantation. The objective of this study was to estimate the variability, divergence and genetic and phenotypic correlations for biochemicals traits in seeds of mother trees of aroeira (Myracrodruon urundeuva Fr. All) to establish ex situ conservation strategies. Genetic and statistical parameters were obtained based on the REML/BLUP procedure. The genetic differences were significant for all traits. The genetic variation coefficient was greater than 15% (carbohydrate). The heritability average of genotypes (> 0.98) and accuracy (> 99%) were high in starch. Genetic and phenotypic correlations between biochemicals compounds were of low magnitude (< 0.29 - starch and prolamin). There was formation of nine heterotic groups and selection of 50% of the mother trees deduced a gain of 15.84% by Mulamba-Mock selection index. Therefore, the natural population of M. urundeuva has broad base genetic and can be used to establish a progeny test as a form of genetic conservation ex situ.
Keywords: chemical composition; genetic parameters; Myracrodruon urundeuva; forest seeds